2010
DOI: 10.4049/jimmunol.1001095
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1: A Central Player in the Anti-Inflammatory and Neuroprotective Role of Microglia

Abstract: The brain microenvironment is continuously monitored by microglia with the detection of apoptotic cells or pathogens being rapidly followed by their phagocytosis to prevent inflammatory responses. The protein annexin A1 (ANXA1) is key to the phagocytosis of apoptotic leukocytes during peripheral inflammatory resolution, but the pathophysiological significance of its expression in the CNS that is restricted almost exclusively to microglia is unclear. In this study, we test the hypothesis that ANXA1 is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
209
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(234 citation statements)
references
References 73 publications
10
209
0
7
Order By: Relevance
“…To further investigate the mechanism whereby recombinant ANXA1 could rescue the permeability deficit seen in AnxA1 −/− mice or in AS clones, we analyzed the role of FPR2, which we have previously shown to mediate the actions of ANXA1 in different cellular contexts (14,17,18). By using flow cytometry, we confirmed the presence of FPR2 on the surface of hCMEC/D3 cells (Fig.…”
Section: Anxa1 Paracellular Permeability Is Mediated By An Interactiomentioning
confidence: 67%
See 1 more Smart Citation
“…To further investigate the mechanism whereby recombinant ANXA1 could rescue the permeability deficit seen in AnxA1 −/− mice or in AS clones, we analyzed the role of FPR2, which we have previously shown to mediate the actions of ANXA1 in different cellular contexts (14,17,18). By using flow cytometry, we confirmed the presence of FPR2 on the surface of hCMEC/D3 cells (Fig.…”
Section: Anxa1 Paracellular Permeability Is Mediated By An Interactiomentioning
confidence: 67%
“…From each paraffin block, 8-μm sections were cut and used for immunohistochemistry as described later. Human plasma samples from patients with MS and healthy donors were used to measure ANXA1 content by ELISA as reported previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, knockout of the putative PS receptor in mice prevents developmental neuronal loss leading to pathologically enlarged brains (48), and microglia are known to mediate the loss of neurons in the developing mouse cerebellum and hippocampus (49,50). These findings are suggestive of microglia or microglial phagocytosis contributing to neuronal death in mammals, and using immortalized cell lines, a recent study has reported the phagocytosis of The Journal of Immunology"normal" neurons by LPS-or amyloid-activated microglia (51). However, whether the inhibition of phagocytosis can prevent neuronal death has so far not been tested.…”
Section: Discussionmentioning
confidence: 87%
“…The FPR family of proteins are G protein-coupled, pattern recognition receptors. Therefore, exogenous ANXA1 can act on FPRs to dampen inflammatory monocyte activation (22) and resolve inflammation (23,24).…”
Section: T He Tlrs Are Important Pattern Recognition Receptors (Prrs)mentioning
confidence: 99%